MANAJEMEN KLUB ATLETIK KOTA PONTIANAK - Winokus Roymondo; Eka Supriatna; Edi Purnomo (Universitas Tanjungpura, 2020)
AbstractThis research is descriptive quantitative research with survey research conducted form at champion runner club pontianak city. The problem in this research was the decreased performance of champion runner club at National sports weeks championship in 2012 to 2016. The formulation of the problem in research was how the management of planning, organizing, actuating and controlling of the athletic club CRC Pontianak city. This study aims to determine the management of planning, organizing, actuating and controlling of the athletic club CRC pontianak city. The data used in this study was the questionnaire data and documentation. Research instruments test was used was the validity and reliability. The population in this study was a athletics club champion runner club taken 31 samples consisting of administrators, coaches, athletes and parents of athletes. Data were analyzed using descriptive statistics with SPSS version 25 and Microsoft Excel 2013. The final results of data analysis using percentage. Results from this study showed that the management of the champion runner club pontianak city athletic club, planning and organizing categorized quite decent with 53.6% planning and organizing 56% whereas the Actuating categorized with good at 77.9% and very good Controlling categorized with 96, 8%.Keywords: Management planning, organizing, actuating, controlling.